Statin use and risk of gallstone disease: A meta‐analysis. Issue 9 (12th November 2014) - Kan, He‐Ping; Guo, Wen‐bin; Tan, Yong‐Fa; Zhou, Jie; Liu, Cun‐dong; Huang, Yu‐Qi
<x xml:space="preserve">Abstract</x> Aim There is emerging evidence from animal and human studies that current statins can decrease the formation of gallbladder cholesterol gallstones and subsequently decrease the risk of gallstone disease, but consistent results have not been reported. We performed a meta‐analysis to provide an overview of the relevant studies. Methods Relevant studies published between January 1980 and February 2014 were identified by searching Medline, Embase and the Cochrane Library. Studies were selected using a priori defined criteria. The strength of the relationship between statin use and risk of gallstone disease was assessed by adjusted odds ratio (OR). Results A total of 622 868 participants from six studies (four case–control studies, one cohort study and one cross‐sectional study) were identified in this meta‐analysis. The studies provided adjusted overall OR estimates for current statin use versus non‐use, leading to a pooled OR of 0.86 (95% confidence interval [CI], 0.77–0.97; P < 0.001). The overall OR of population‐based case–control studies and cholecystectomy due to gallstone disease were 0.83 (95% CI, 0.73–0.95; P = 0.0131) and 0.78 (95% CI, 0.74–0.82; P = 0.615), respectively. Conclusion There is evidence that current statin use lowers the risk of gallstone disease compared with non‐use, especially for cholecystectomy due to gallstone disease. Low statin use (1–4 prescriptions) did not decrease the risk of gallstone disease, but moderate and high statin use significantly decreased the risk. Further multicenter and better controlled studies are needed to confirm these findings.